The Effect of China’s Political Reforms on Taiwanese Third Sector : Qualitative Study of Religion Affiliated Taiwanese NGOs: Border-crossing Civil Society across the Taiwan Strait - Kastepohja, Jussi (My University, 2020)
This thesis investigates Taiwanese and Chinese civil societies that operate at opposite shores of the Taiwan Strait and in between two competing political administrations. The main focus of this thesis is to explore the meanings that Taiwanese NGO workers and leaders give to their work in Taiwanese civil society in those situations where their work with Chinese civil society is overlapping. Having its basis in two restrictive mainland Chinese political regulations from years 2016 and 2018, it examines how these two legislative changes in the PRC affect the working life in the NGOs across the Strait. This research uses secondary sources about Taiwan question, religion and civil society in East Asian contexts as the reciprocal focus point to the primary sources of semi-structured qualitative interview data. Based on the methodology of phenomenology and social constructivism, the main emphasis is in the content and interpretations of the Taiwanese NGO workers within their working life particularly in Xi Jinping era. The thesis uses qualitative semi-structured interviews as the main data, which is analysed by qualitative content analysis. According to the research data, China’s ONGO Law in 2016 and Religious Affairs Regulations in 2018 changed the Taiwanese NGO workers’ daily working life depending on the sector and size of the NGO they were working at. The results indicate that the bigger INGO doing humanitarian work was more affected by the ONGO Law of 2016, whereas the smaller NGOs working at the spheres of media, religion and culture were more affected by the Religious Affairs Regulation in 2018. By the ongoing conversation with the earlier research about Taiwan question and the Taiwanese and Chinese civic sectors, this thesis enables the voices of the workers in Taiwanese NGOs to be heard in the ambiguous political situation across the Strait. The theme of indirectedness was highlighted in the research results, which indicates the invisible interdependence relation between Taiwan and China. Subsequent research should be made in order to understand the ways, how China affects Taiwan in different indirect means. This thesis serves as the beginning chapter of what these changes around this political hot-spot indicate for the future of China’s rise in the global arena and opens the possibility to future investigations around topics of interconnected East Asian civil societies and politically intertwined global third sector.
Keywords: Civil society, interdependence, religion, third sector, Taiwan, China.